A Critique of Dante's Influence on Sanā’ī in the Research of Orientalists - Iman Mansub Basiri; Mahzad Sheikholislami; Hossein Hasani Dargah (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
When Reynold Alleyne Nicholson mentioned some similarities between Dante's Divine Comedy and Sanā’ī’s Seyr al-‘ebād in his article "A Persian forerunner of Dante", the belief that Dante has been influenced, in the creation of his eternal work, by the Sanai’s opus came into some minds. The publication of the famous book of Spanish scholar Miguel Asin Palacios La Escatologia Musulmana en la «Divina Comedia» and the discovery of two old Latin and French manuscripts of Prophet Muhammad`s Me’rāj (Liber Scalae Machometi) in the Oxford library and the National Library of Paris fortified this belief. The approach of this research, which differentiates it from similar studies, is analyzing briefly the contribution of Arabic, Latin, and Persian sources that have influenced diachronically the two mentioned works. On the other hand, the emphasis of the present article, contrary to the similar works, does not affect the similarities or differences in the thematic structure of these two works, but we tried to analyze the most important sources that produced similar or identical themes in the works of both authors.